Performance Limitations of Wide‐Gap (Ag, Cu)(In, Ga)Se2 Thin‐Film Solar Cells. Issue 9 (20th July 2021) - Keller, Jan; Pearson, Patrick; Shariati Nilsson, Nina; Stolt, Olof; Stolt, Lars; Edoff, Marika
Abstract : The effect of absorber stoichiometry in (Ag, Cu)(In, Ga)Se2 (ACIGS) solar cells with bandgaps ( E g ) > 1.40 eV is studied on a large sample set. It is confirmed that moving away in composition from ternary AgGaSe2 by simultaneous reduction in Ga and Ag content widens the chalcopyrite single‐phase region and thereby reduces the amount of ordered vacancy compounds (OVCs). As a consequence, a distortion in current−voltage characteristics, ascribed to OVCs at the back contact, can be successfully avoided. A clear anticorrelation between open‐circuit voltage ( V OC ) and short‐circuit current density ( J SC ) is detected with varying absorber stoichiometry, showing decreasing V OC and increasing J SC values for [I]/[III] > 0.9. Capacitance profiling reveals that the absorber doping gradually decreases toward stoichiometric composition, eventually leading to complete depletion. It is observed that only such fully depleted samples exhibit perfect carrier collection, evidencing a very low diffusion length in wide‐gap ACIGS films. The results indicate that OVCs at the surface play a minor or passive role for device performance. Finally, a solar cell with V OC  = 0.916 V at E g  = 1.46 eV is measured, which is, to the best of our knowledge, the highest value reported for this bandgap to date. Abstract : The effect of absorber stoichiometry in wide‐gap ACIGS solar cells is revised. A strong and opposing effect on J SC and V OC is found. With increasing [I]/[III] values > 0.9, V OC continuously decreases, while charge carrier collection increases. Observations can be explained by decreasing absorber doping toward stoichiometric composition. The results indicate a very low diffusion length in wide‐gap ACIGS films.